Evaluation of Renal and Cardioprotective Potential of the Biofield Energy Treated Proprietary Test Formulation on L-NAME and High Fat Diet-Induced Cardiovascular Disorders in Sprague Dawley Rats - Mahendra, Kumar Trivedi; Alice, Branton; Dahryn, Trivedi; Snehasis, Jana (Journal of Nephrology Advances, 2021)
The aim of this study was to evaluate the impact of Biofield Energy Treated/Blessed Proprietary Test Formulation and Biofield Energy Treatment/Blessing per se on kidney biomarkers on L-NAME and high fat diet (HFD)-induced cardiovascular disorders in Sprague Dawley rats. In this experiment, the functional kidney biomarkers such as epinephrine/adrenaline, inducible nitric oxide synthase (iNOS), angiotensin-II, C-reactive protein (CRP), and renin were measured using ELISA assay. A test formulation was formulated including minerals (magnesium, zinc, copper, calcium, selenium, and iron), vitamins (vitamin C, vitamin B6, vitamin B12, vitamin B9, and vitamin D3), cannabidiol (CBD) isolate, Panax ginseng extract, and β-carotene. The components of the test item were divided into two; one section was defined as the untreated test formulation, while the other part and three group of animals received Mr. Mahendra Kumar Trivedi’s Biofield Energy healing/Blessing remotely for about 3 minutes. The results showed that the level of adrenaline was reduced by 31.62%, 19.58%, 34.32%, 37.07%, and 29.87% in the G5 (L-NAME + HFD + the Biofield Energy Treated test formulation), G6 (L-NAME + HFD + Biofield Energy Treatment per se to animals from day -15), G7 (L-NAME + HFD + the Biofield Energy Treated test formulation from day-15), and G8 (L-NAME + HFD + Biofield Energy Treatment per se plus the Biofield Energy Treated test formulation from day-15), and G9 (L-NAME + HFD + Biofield Energy Treatment per se animals plus the untreated test formulation) groups, respectively as compared to the disease control group (G2). Moreover, the level of iNOS was reduced by 56.76%, 49.51%, 61.79%, 57.63%, and 62.44% in the G5, G6, G7, G8, and G9 groups, respectively, as compared to the disease control group (G2). Additionally, the level of angiotensin-II was decreased by 41.09%, 34.92%, 60.65%, 53.28%, and 60.09% in the G5, G6, G7, G8, and G9 groups, respectively, as compared to the G2 group. The level of CRP was decreased by 47.21%, 38.89%, 59.81%, 55.52%, and 64.02% in the G5, G6, G7, G8, and G9 groups, respectively as compared to the G2 group. Besides, the level of renin was decreased by 20.27%, 20.13%, 12.99%, and 25.73% in the G5, G7, G8, and G9 groups, respectively as compared to the G2 group. Overall, the data suggested significance improvement of vital functional kidney biomarkers of the Biofield Energy Treated/Blessed test formulation and Biofield Energy Treatment per se along with preventive measure on the animal with respect to various pathological conditions that might be beneficial various types of cardiovascular disorders. Therefore, the results showed the significant slowdown the inflammation-related cardiovascular disease progression and its complications/symptoms in the preventive Biofield Energy Treatment group per se and/or Biofield Energy Treated/Blessed Test formulation groups (viz. G6, G7, G8, and G9).
Keywords: Biofield Treatment; The Trivedi Effect®; ELISA; High Fat Diet; Cardiovascular Disorders; adrenaline; iNOS; Angiotensin-II; Renin; C-reactive protein